Why "intergenerational feminist media studies"?. Issue 4 (3rd July 2016) - Winch, Alison; Littler, Jo; Keller, Jessalynn
Abstract: Feminism and generation are live and ideologically freighted issues that are subject to a substantial amount of media engagement. The figure of the millennial and the baby boomer, for example, regularly circulate in mainstream media, often accompanied by hyperbolic and vitriolic discourses and affects of intergenerational feminist conflict. In addition, theories of feminist generation and waves have been and continue to be extensively critiqued within feminist theory. Given the compelling criticisms directed at these categories, we ask: why bother examining and foregrounding issues of generation, intergeneration, and transgeneration in feminist media studies? Whilst remaining sceptical of linearity and familial metaphors and of repeating reductive, heteronormative, and racist versions of feminist movements, we believe that the concept of generation does have critical purchase for feminist media scholars. Indeed, precisely because of the problematic ways that is it used, and the prevalence of it as a volatile, yet only too palpable, organizing category, generation is both in need of continual critical analysis, and is an important tool to be used—with care and nuance—when examining the multiple routes through which power functions in order to marginalize, reward, and oppress. Exploring both diachronic and synchronic understandings of generation, this article emphasizes the use of conjunctural analysis to excavate the specific historical conditions that impact upon and create generation. This special issue of Feminist Media Studies covers a range of media forms—film, games, digital media, television, print media, as well as practices of media production, intervention, and representation. The articles also explore how figures at particular lifestages—particularly the girl and the aging woman—are constructed relationally, and circulate, within media, with particular attention to sexuality. Throughout the issue there is an emphasis on exploring the ways in which the category of generation is mobilized in order to gloss sexism, racism, ageism, class oppression, and the effects of neoliberalism.